La mise en vedette de la vie privée des personnalités politiques dans les médias allemands (1990-2004) - Holtz-Bacha, Christina (Temps des Medias, 2008)
In Germany, the right to privacy also applies to public figures. At the same time it is acknowledged that the public has a legitimate interest in how politicians behave in their private life if that pertains to the way they carry out their duties. Until recently, the media kept out of the private life of politicians and thus enjoyed a fruitful symbiosis where information is exchanged for decency. Several cases from the last years indicate that what was once regarded a journalistic taboo, no longer seems to hold. While commercialisation of the media is one reason for this new development in the relation between journalists and politicians, changes in the way politicians present themselves to the public are another. Altogether, the instrumenta liza tion of the private for political strategy has played a major role for the waning restraint of the media vis-a-vis the private sphere of politicians.
WiSo-Import:2015-03-26:1527
Keywords: Transformation; La mise en vedette de la vie privée des personnalités politiques dans les médias allemands (1990-2004)